Social work practice for COVID-19 in the acute hospital setting: Recommendations for psychosocial assessment. (7th January 2022) - Ready, James; Lewis, Greg; Barr-Lynch, Sandra; Casey, Amanda; King, Ashley; Wojciechowski, Lisa
Abstract: The global coronavirus SARS-CoV2 (COVID-19) pandemic outbreak caused immediate, far-reaching social schisms and created unprecedented challenges for hospital social work services worldwide. Existing hospital disaster plans were inadequately equipped for pandemics and organisational plans needed to quickly adapt to respond to the increased clinical demands and unique logistical considerations triggered by the virus. Literature reviews provided little in the way of precise guidance for practitioners. Hospital social workers responded not only to a new cohort of patients, but also to all patients affected by the societal repercussions of the pandemic and by governments' attempts to mitigate the impacts of the virus. Psychosocial assessments, the bedrock of social work intervention, needed to adapt and evolve to encompass and address the exacerbation of existing social risks in new ways. This article originated from the authors' interest in identifying practice implications for hospital social work during the COVID-19 pandemic. The authors briefly outline the distinct impact of COVID-19 on psychosocial issues such as domestic and family violence, elder abuse, child protection, financial stress and social isolation. They create a forum of international hospital social work centres to develop a consensus approach for addressing these issues in the context of a social work psychosocial assessment. Abstract : The global COVID-19 pandemic stretched hospital resources across the globe and presented unique challenges to social work services. Disaster response plans were not adequately applicable given their time-limited nature. The broader social repercussions of the pandemic and governments' approaches to mitigating it meant that the cornerstone of social work intervention in hospitals—psychosocial assessments—needed to consider the aggravation of social risks in entirely new ways. The authors briefly outline the impacts of the pandemic and response on psychosocial issues such as domestic and family violence, elder abuse, child protection, financial stress and social isolation. They consult international hospital social work centres and develop an agreed approach for addressing these issues in the context of a social work psychosocial assessment.